2021
DOI: 10.3390/ani11010208
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase Inhibition Decreases the Expression of Collagen and Metallopeptidase in Mare Endometria under In Vitro Conditions

Abstract: Neutrophils can originate neutrophil extracellular traps (NETs). Myeloperoxidase (MPO) is a peroxidase found in NETs associated to equine endometrosis and can be inhibited by 4-aminobenzoic acid hydrazide (ABAH). Metallopeptidases (MMPs) participate in extracellular matrix stability and fibrosis development. The objectives of this in vitro work were to investigate, in explants of mare’s endometrium, (i) the ABAH capacity to inhibit MPO-induced collagen type I (COL1) expression; and (ii) the action of MPO and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 63 publications
1
21
0
2
Order By: Relevance
“…The proteases (ELA and CAT) and peroxidase (MPO) found in NETs were recently shown to induce COL1 expression in equine endometrium, suggesting NETs enzymes involvement in the pathophysiology of equine endometrial fibrosis [ 9 , 11 , 12 , 13 , 14 ]. However, not only equine endometrosis seems to be affected by profibrotic effects of NETs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The proteases (ELA and CAT) and peroxidase (MPO) found in NETs were recently shown to induce COL1 expression in equine endometrium, suggesting NETs enzymes involvement in the pathophysiology of equine endometrial fibrosis [ 9 , 11 , 12 , 13 , 14 ]. However, not only equine endometrosis seems to be affected by profibrotic effects of NETs.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrosis treatment has been challenging, with no effective treatment found so far. To make progress on endometrosis treatment, we have also shown that ELA, CAT or MPO fibrotic effect on the mare endometrium can be inhibited in vitro by sivelestat sodium salt, β-keto-phosphonic acid, or 4-aminobenzoic acid hydrazide, respectively [ 12 , 13 , 14 ]. These promising results are the latest advances in equine endometrosis putative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations